Pengelolaan Arsip Dinamis Di Dinas Kearsipan Provinsi Sumatera Selatan - Novia Febriyanti (UIN Sumatera Utara, 2019)
The purpose of this study is to find out the management of dynamic records and archival retrieval systems at the Archives Office of South Sumatra Province. This study uses the observation method with data collection techniques in the form of interviews, namely Mr. H. Ir. Muhammad Sidik Faisol, M.Sc as a guest speaker. The results obtained from this study are known that the management of dynamic records in the Office of Archives of South Sumatra Province uses a classification system as a means of structuring the archives so that in the archive storage will be arranged based on classification numbers. The archive destruction method used was enumeration, this method was chosen because it was considered more environmentally friendly than the combustion method. And for the file retrieval system, still by manual or by using a computer system.